Concomitant tricuspid surgery for moderate tricuspid regurgitation improves survival in left-sided valve surgery – a meta-analysis - Anupama Barua; Nicholas Wong; Shubham Jain; Mohsin Uzzaman; Prakash Nanjaiah; Ravish Jeeji; Lognathen Balacumaraswami (Journal of Cardiothoracic Surgery)
Abstract Objectives There is controversy over the optimal management of moderate tricuspid valve regurgitation during left-sided valve surgery due to the paucity of robust evidence for enhanced outcomes from concomitant tricuspid valve repair. Hence, we assessed the literature to compare clinical outcomes in patients undergoing left-sided valve procedures either with or without tricuspid valve repair surgery. Methods We performed a literature search using MEDLINE, EMBASE, Scopus and Web of Science. We identified articles to evaluate primary outcomes of both, cardiac and overall mortality. Secondary outcomes included stroke, wound infection, reoperation, new-onset atrial fibrillation, renal failure, duration of intensive care stay and permanent pacemaker implantation. All analysis was done using the random effects model. Results A total of 36 studies were included with 76,249 patients. There was significant reduction in cardiac mortality (p < 0.0001) with concomitant tricuspid valve repair despite higher CPB (p < 0.00001) and X-Clamp times (p < 0.00001). There was no significant difference in overall mortality. There was significantly lower postoperative tricuspid regurgitation (p < 0.00001) with concomitant tricuspid repair. There were no differences in postoperative stroke, wound infection, atrial fibrillation, renal failure, and intensive care unit duration of stay between the two groups. Conclusions Concomitant tricuspid valve surgery for moderate tricuspid regurgitation during left-sided valve surgery offers improved survival benefit due to significant decrease in cardiac mortality. Additionally, this strategy results in significant decrease in late tricuspid regurgitation with no increase in morbidity.